Psikoedukasi: Optimalisasi Pertumbuhan Anak Stunting Bagi Orang Tua Muda di Puskesmas Sekaran - Prihastuty, Rahmawati; Purwanto, Edi; Mabruri, Moh. Iqbal; Firdaus, Aina Aulia; Kusumamahanani, Fatma; Shelma , Ismy Alifia; Pramesty, Dewi Indah; Maryam (Jendela Akademika, 2023)
Stunting is a problem that being intensively addressed by the government and priority program at Puskesmas Sekaran which is the background for this Community Service activity. The existence of stunting cases in Gunungpati is caused by various factors, such as unprepared pregnancies, low birth weight babies, and low levels of exclusive breastfeeding. The aim of this activity is to increase young parents' knowledge about stunting, parenting, healthy homes and child nutrition so that it can help reduce stunting cases. This is due to several causal factors based on insufficient knowledge. Therefore, the method used is psychoeducation. The result of this service is an increase in the knowledge of young parents in the Gunungpati area as seen from the significant difference in results on the pre-test and post-test. The advice that can be given is that it would be better if this service program was carried out long term and sustainably. Apart from that, the target of activities should be expanded so that they can provide education not only to young parents, but also to the surrounding community so that they can participate in reducing stunting rates.